Overwhelming and cross-party public support for robust tobacco control measures to achieve a Smokefree Aotearoa New Zealand: findings from a national survey - Richard Edwards; Ella Iosua; Amanda Dodd; Andrew Gray; Rana Peniamina; Louise Signal; Bronwen McNoe (New Zealand Medical Journal, 2026)
aim: Tobacco is a leading cause of preventable disease, mortality and health inequity in Aotearoa New Zealand where smoking prevalence decline has stalled. Further reductions will likely require tobacco control measures beyond business-as-usual approaches. We report survey support for tobacco control and vaping regulation policies. methods: We recruited adults from an online panel using quota sampling. We assessed support using a structured questionnaire for: reducing nicotine content in smoked tobacco products; restricting retail availability of tobacco/vaping products; a tobacco-free generation policy; raising the minimum legal age of sale for tobacco and vaping to 21 years; introducing tobacco industry levies; and ending legal sales of smoked tobacco products. results: After oversampling, we received 1,635 participant responses, including n=385 from Māori (23.5%, unweighted) and n=368 from Pacific people (22.5%, unweighted). We found strong majority (70–85%) support for all nine tobacco control/vaping regulation policies. Support was mostly similar by age group, gender, prioritised ethnicity and voting intention, including strong support for all policies among supporters of parties making up the current Coalition Government, and among 18–20-year-olds for the tobacco-free generation and raising the legal age of sale to 21 years policies. conclusion: The findings demonstrate overwhelming public support for more robust tobacco control interventions. Politicians of all political parties should prioritise and be held accountable for introducing strong, effective tobacco control measures in order to achieve the Smokefree Aotearoa goal for all peoples. This will greatly improve population health and reduce health inequities, prevent the social, environmental and economic costs of tobacco smoking, honour Te Tiriti o Waitangi and protect future generations from the scourge of tobacco.